Molecular chaperones in Parkinson's disease - present and future - Ebrahimi-Fakhari, Darius; Wahlster, Lara; McLean, Pamela J. (Journal of Parkinson's Disease, 2011)
Parkinson's disease, like many other neurodegenerative disorders, is characterized by the progressive accumulation of pathogenic protein species and the formation of intracellular inclusion bodies. The cascade by which the small synaptic protein α-synuclein misfolds to form distinctive protein aggregates, termed Lewy bodies and Lewy neurites, has been the subject of intensive research for more than a decade. Genetic and pathological studies in Parkinson's disease patients as well as experimental studies in disease models have clearly established altered protein metabolism as a key element in the pathogenesis of Parkinson's disease. Alterations in protein metabolism include misfolding and aggregation, post-translational modification and dysfunctional degradation of cytotoxic protein species. Protein folding and re-folding are both mediated by a highly conserved network of molecules, called molecular chaperones and co-chaperones. In addition to the regulatory role in protein folding, molecular chaperone function is intimately associated with pathways of protein degradation, such as the ubiquitin-proteasome system and the autophagy-lysosomal pathway, to effectively remove irreversibly misfolded proteins. Because of the central role of molecular chaperones in maintaining protein homeostasis, we herein review our current knowledge on the involvement of molecular chaperones and co-chaperones in Parkinson's disease. We further discuss the capacity of molecular chaperones to prevent or modulate neurodegeneration, an important concept for future neuroprotective strategies and summarize the current progress in preclinical studies in models of Parkinson's disease and other neurodegenerative disorders. Finally we include a discussion on the future potential of using molecular chaperones as a disease modifying therapy.
Gesehen am 04.04.2022